Synergistic enhancement of production of proinflammatory cytokines of human peripheral blood monocytes by anti-Sm and anti-RNP antibodies - Matsueda, Yu (PLoS One, 2018)
The present study was performed to elucidate the roles of serum anti-Sm antibodies in the pathogenesis of systemic lupus erythematosus (SLE). Highly purified peripheral blood monocytes obtained from healthy donors were cultured in the presence of monoclonal anti-Sm antibody (anti-Sm mAb), monoclonal anti-U1-RNP antibody (anti-RNP mAb) or control murine IgG1 or IgG3. After various periods of incubation, levels of IL-6 and TNF-α in the culture supernatants were measured by ELISA and the expression of mRNA for various molecules in monocytes was determined using RT-PCR. Flow cytometry analysis confirmed the bindings of anti-Sm mAb and anti-RNP mAb on viable human monocytes. Both anti-Sm mAb and anti-RNP mAb significantly increased the production of IL-6 and TNF-α of human monocytes in a dose-dependent manner, although the latter was more potent than the former. Of note, anti-Sm mAb synergistically enhanced the production and mRNA expression of IL-6 and TNF-α of human monocytes in the presence of anti-RNP mAb. Notably, anti-RNP mAb, but not anti-Sm mAb, significantly enhanced the mRNA expression of RelA in human monocytes. Finally, anti-Sm mAb still up-regulated the IL-6 production of monocytes in the presence of anti-RNP mAb under the influence of N-acetyl cysteine or pyrrolidine dithiocarbamate that totally abrogated the IL-6 production provoked by anti-Sm mAb alone in the absence of anti-RNP mAb. These results demonstrate that anti-Sm and anti-RNP antibodies synergistically up-regulate the expression of IL-6 and TNF-α in human monocytes. The data also suggest that the effect of anti-Sm in the synergy with anti-RNP might not involve NFkB activation.